Analysis of Factors Affecting Customer Loyalty of Sharia Bank Sub-Branch of Padang City: Analisis Faktor-Faktor Yang Mempengaruhi Loyalitas Nasabah Bank Syariah Cabang Pembantu Kota Padang - eliza eliza; zefriyenni zefriyenni (International Journal of Management and Business (IJMB), 2022)
The banking business is a service business based on the principle of trust, so that the problem of service quality becomes a very decisive factor in business success. Economic progress affects people's lives. The increase in the social and economic status of the community results in changes in their behavior and lifestyle. These changes ultimately affect the taste of satisfaction with a product. This study aims to examine the effect of service quality, trust, and commitment, either partially or simultaneously on customer loyalty at Bank Syariah Mandiri Sub-Branch Office Ulak Karang Padang. Based on the results of the study, it was found that, either partially or simultaneously, it has an influence between service quality, trust, and commitment to customer loyalty. Likewise, the variance up and down the influence of the independent variable on the dependent variable is 81.4 percent, meaning that it has a very strong influence.